Economics, evolution and the state - Dopfer Kurt (Cheltenham Edward Elgar, 2005)
Focusing on the field of evolutionary economic policy, this book highlights the interface between the state, markets, and the evolutionary complexity of modern economies. It explores the possibilities and limitations of governance, and also provides a di
Keywords: Evolutionary economic policy; Evolutionary economics